Interconnections: A systems history of science, technology, leisure, and fear - Fred Phillips (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
It is well known that technological change causes social change, and vice versa. Using system and historical perspectives, this article examines that truth at a finer level of specificity, namely, that social perceptions of interconnectedness influence the progress of science and technology, and that conversely, as 21st-century technology makes us in fact more connected, society's anxieties shift. From the science/technology side, we look at interdisciplinary research, system and complexity theory, quantum tech, and the Internet, exploring how these interact and cause changes in social attitudes-fears, conspiracy theories, political polarization, and even entertainment trends-some of which are surprising, and some dangerous. The article's systems view helps make sense of current environmental, political, and psychological crises. It combines original ideas with those of several prominent thinkers, to suggest constructive actions.
Keywords: 650; history of science and technology; science and society; systems; terror